Bulk chemical controls on metamorphic monazite growth in pelitic schists and implications for U-Pb age data - Fitzsimons, Ian; Kinny, Peter; Wetherley, S.; Hollingsworth, David (John Wiley and Sons, 2005)
Several petrographic studies have linked accessory monazite growth in pelitic schist to metamorphic reactions involving major rock-forming minerals, but little attention has been paid to the control that bulk composition might have on these reactions. In this study we use chemographic projections and pseudosections to argue that discrepant monazite ages from the Mount Barren Group of the Albany?Fraser Orogen, Western Australia, reflect differing bulk compositions. A new SHRIMP U-Pb monazite age of 1027 8 Ma for pelitic schist from the Mount Barren Group contrasts markedly with previously published SHRIMP U-Pb monazite and xenotime ages of c. 1200 Ma for the same area. All dated samples experienced identical metamorphic conditions, but preserve different mineral assemblages due to variable bulk composition. Monazite grains dated at c. 1200 Ma are from relatively magnesian rocks dominated by biotite, kyanite and/or staurolite, whilst c. 1027 Ma grains are from a ferroan rock dominated by garnet and staurolite. The latter monazite population is likely to have grown when staurolite was produced at the expense of garnet and chlorite, but this reaction was not intersected by more magnesian compositions, which are instead dominated by monazite that grew during an earlier, greenschist-facies metamorphic event. These results imply that monazite ages from pelitic schist can vary depending on the bulk composition of the host rock. Samples containing both garnet and staurolite are the most likely to yield monazite ages that approximate the timing of peak metamorphism in amphibolite-facies terranes. Samples too magnesian to ever grow garnet, or too iron-rich to undergo garnet breakdown to staurolite, are likely to yield older monazite, and the age difference can be significant in terranes with a polymetamorphic history.